2023
DOI: 10.3390/bs13040333
|View full text |Cite
|
Sign up to set email alerts
|

A Lack of Focus, Not Task Avoidance, Makes the Difference: Work Routines in Procrastinators and Non-Procrastinators

Abstract: Procrastination may be seen as the outcome of a learning history of delaying the onset of task execution and its completion, both in terms of time and effort. In this study, we examined the performance of 55 university students who carried out two writing tasks consisting of summarizing two academic papers, each within a different time slot (i.e., five vs. three days to complete). The two assignments were part of the class activity and were perceived by participants as homogeneous in terms of text appreciation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Our final hypothesis (H4), which states that there would be a relationship between the types of tasks (project, written assignments, presentations) and the commitment to the course can, therefore, be accepted. Research has shown that task aversion or level of unpleasantness, perceptions of boredom or uninteresting a student associates with a task could be a significant factor in student delay in starting, working on, and finishing assignments [ 19 , 33 , 34 ]. It is demonstrated in our study that students are more likely to submit the task on time when it is related to the presentation as compared to written assignments which also recorded a high percentage and frequency of no submission.…”
Section: Discussionmentioning
confidence: 99%
“…Our final hypothesis (H4), which states that there would be a relationship between the types of tasks (project, written assignments, presentations) and the commitment to the course can, therefore, be accepted. Research has shown that task aversion or level of unpleasantness, perceptions of boredom or uninteresting a student associates with a task could be a significant factor in student delay in starting, working on, and finishing assignments [ 19 , 33 , 34 ]. It is demonstrated in our study that students are more likely to submit the task on time when it is related to the presentation as compared to written assignments which also recorded a high percentage and frequency of no submission.…”
Section: Discussionmentioning
confidence: 99%